Ethics in Islamic Economics - Boutayeba, Faiçal; Benhamida, Mohammed; Souad, Guesmi (Annales. Etyka w Życiu Gospodarczym, 2014)
The purpose of this contribution is to shed some light on the inter-relationshipsbetween ethics and economics in Islamic religion, and mainly to assert that ethicsconstitute endogenous phenomena in Islamic economics. In Islam, economic behavioursand transactions cannot be separated from ethics and values. The Islamicprinciples are intended to govern, direct and control human beings’ behaviours intheir daily economic lives. They are aimed at helping people to distinguish betweengood and bad things while they do any economic activity.It is worth noting that the moral values in Islamic economics are derivedfrom the main sources of Islam namely: the Quran (the holy book of Islamic religion)and Sunnah (the teachings and behaviours of the prophet of Islam: MuhammadPBUH 570-632 AD). Both of them represent the principal pillars of Shariah(Islamic laws and guidelines), which is seen by Muslims as the proper way tohappiness, not only in economic life but in all aspects of life.